Performance of an internet of things based plant monitoring and irrigation system using solar energy - Affzani Md Rozani, Md Azim; Azha Mohd Annuar, Khalil; Razali Mohamad Sapiee, Mohd; Kumar Debnath, Sanjoy (Bulletin of Electrical Engineering and Informatics, 2025)
This paper aims to present an internet of things (IoT) based plant monitoring and irrigation system powered by solar energy. The system enhances plant care by continuously monitoring environmental conditions such as soil moisture, temperature and humidity with real data displaye via the Blynk platform. User can remotely monitor and control irrigation through interactive widgets, ensuring efficient plant management. By integrating solar energy, the system operates sustainably, and reduce reliance on conventional electricity. Performance evaluation demonstrates a temperature sensor accuracy of 98%, a humidity sensor accuracy of 95% and soil moisture sensor error margin of 2-3%. Experiment results indicate improved plant growth of 7-8% compared to traditional farming practices, showcasing the system’s potential for increased productivity and conversion. This research highlight the benefits of combining IoT and renewable energy to offer an innovative, and eco-friendly solution for agricultural management.